(untitled) (Bangladesh Journal of Agricultural Research, 2018)
This study was conducted to determine the effects of organic materials to remediate contaminated soil with heavy metals. A pot study was performed by growing maize (Zea mays) in metal contaminated soil (10 kg pot-1) and soils amendments with cow manure dust, poultry manure dust, vermicompost dust, fern dust, water hyacinth dust, mustard stover dust and barnyard grass dust each at 5 g kg-1 soil. The results showed that Pb, Cd, Ni, Cr and Co uptake by maize depended on the organic materials type. Water hyacinth dust, fern dust, mustard stover dust, and barnyard grass dust addition led to decreased metal content in maize, and this decrease was better expressed with 20.5 to 33.3% for fern dust, 17.3 to 22.0 % for water hyacinth, 18.6 to 21.3% for mustard stover dust, 17.33 to 20.5% for barnyard grass dust. Cow manure dust, poultry manure dust and vermicompost dust led to increased metal content in the maize, and this increase was 6.80 to 18.7 % for cow manure, 18.9 to 86.7 % for poultry manure and 17.4 to 16.0 % for vermicompost. The different effectiveness of organic amendment on metal uptake by maize plant could be due to the nature of organic matter where water hyacinth dust, fern dust, mustard stover dust, and barnyard grass dust were mainly originated from plant. On the other hand, cow manure, poultry manure and vermicompost were mainly the excreta collected from cattle, poultry and earthworms. However, immobilization and phytoextraction techniques might be used to remediate soils which are contaminated with heavy metal. Bangladesh J. Agril. Res. 42(4): 589-598, December 2017